Brain, body, and mind : neuroethics with a human face - Glannon, Walter (New York ; Oxford : Oxford University Press, 2011)
Drawing upon recent work in psychiatry, neurology, and neurosurgery, this text develops a phenomenologically inspired conception of neuroscience to explain the brain-mind relation. The mind is shaped not just by the brain but also by the body and how the human subject interacts with the environment.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Keywords: Neurosciences -- Moral and ethical aspects; Bioethics; Medical ethics